Melanoma in patients with mycosis fungoides - Arfenya E. Karamova; Anastasiya A. Vorontsova; Maryanna B. Zhilova; Lyudmila F. Znamenskaya; Rifat R. Saytburkhanov; Kseniya M. Aulova (State Scientific Center of Dermatovenereology and Cosmetology, 2021)
The development of both malignant neoplasms mycosis fungoides and cutaneous malignant melanoma is a rare condition; nevertheless, the literature describes both cases of the development of mycosis fungoides in patients with a primary diagnosis of melanoma and the detection of cutaneous malignant melanoma in patients with T-cell lymphomas of the skin. The question of the effect of previous therapy for mycosis fungoides on the risk of cutaneous malignant melanoma remains controversial. Currently, the world community is considering a possible pathogenetic relationship between these two oncopathologies. The clinical observations of the development of cutaneous malignant melanoma in 2 patients with mycosis fungoides presented in the article emphasize the importance of a thorough clinical and dermatoscopic examination of all pigmented formations for the timely detection of malignant melanocytic neoplasms, the presence of which radically affects the further choice of treatment tactics for patients.